ТЕХНИК-МУҲАНДИСЛИК ФАОЛИЯТИНИ ШАКЛЛАНТИРИШДА ТАЪЛИМГА ТИЗИМЛИ ЁНДАШУВНИНГ МОҲИЯТИ - Рўзиева, Д.С. (SCIENCE and SOCIETY, 2022)
The article gives an idea of the possibilities and effectiveness of the organization of a systematic method of approach to teaching physics in higher educational institutions of technical orientation.
Keywords: system approach; system principles; professional competence; modeling; information environment